Pengetahuan Dan Sikap Calon Pengantin Terhadap Aplikasi Elsimil Di KUA Kecamatan Pahandut - Munanadia, Munanadia (Akademi Kebidanan Bunga Husada Samarinda, 2024)
Stunting in children due to prolonged malnutrition is a form of growth faltering due to the accumulation of inadequate nutrition that lasts from pregnancy to 24 months of age. One specific intervention is carried out by means of nutritional interventions in mothers before and during pregnancy. In this case, the National Population and Family Planning Agency (BKKBN) developed the Elsimil Application, catin must be examined first if there is anemia and malnutrition is encouraged to delay pregnancy until nutrition is sufficient. This application is expected to detect early the potential birth of stunted babies based on the health condition of the catin. based on the results of the health check the application will conduct an automatic assessment to determine the condition of the catin woman is